Faktor-Faktor yang Berhubungan dengan Perkembangan Bahasa Balita di UPTD Kesehatan Baserah Tahun 2016 - Yenny Safitri (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2017)
An important period in the development of the child is a toddler years. leanguage ability  is an indicator of the whole development of the child. Lack of stimulation will cause speech and language disorders even these disorders can be settled. Long-term observation stated that 42.5% children who have speech and language delays at risk of difficulty learning, difficulty reading and writing and will cause less academic achievement overall, in some cases have a low IQ. The purpose of this study was to determine the factors associated with infant language development at Health UPTD 2016. Base quantitative research methods, this kind of research is analytic with study case control design.The population in this study are all mothers who have children in UPTD Health Baserah 2015 are 1248 people, with the samples using a ratio of 1: 1,  43 with a sample of cases and 43 with a control sample, sampling technique using systematic random sampling and data analysis using Chi-Square.The results showed correlation between knowledge with toddler language development, there is a connection with the development of language parenting a toddler, and no socio-economic relations dengann toddler language development. For health workers is expected to provide information to mothers who have children in the prevention and early detection of developmental language  delays.